Influence of apical enlargement in cleaning and extrusion in canals with mild and moderate curvatures - e Borges, Mauricia Ferreira de Almeida; Miranda, Carlos Eduardo Saraiva; Silva, Silvio Rocha Corrêa da [UNESP]; Marchesan, Melissa (FapUNIFESP (SciELO), 2011)
Optical microscopy and morphometric analysis were used in this study to evaluate, in vitro, the cleaning of the apical region in root canals with mild or moderate curvatures subjected to biomechanical preparation with a rotary system, as well as to assess the amount of extruded material to the periapical area. Lateral incisors (n = 32), 16 with curvature angles smaller or equal to 10° (GI) and 16 between 11° and 25° angles (GII) were submitted to Hero 642 rotary instrumentation with different surgical diameters: (A) 30.02 and (B) 45.02. Irrigation was performed at each change of instrument with 5 mL of ultrapure Milli-Q water and the extruded material through the apical foramen was collected. Root cross-sections were subjected to histological analysis by optical microscopy (×40) and the images were evaluated morphometrically using the Image Tool software. Quantification of the extruded material was performed by weighing after liquid evaporation. ANOVA showed no statistically significant differences (p>0.05) among the groups with respect to the procedures used to clean the apical region. Considering the amount of extruded material, the Tukey's HSD showed that canals with mild curvature prepared with the 45.02 surgical diameter showed significantly higher values (p<0.05) that those of the other groups, which were similar between themselves (p>0.05). In conclusion, the effect of cleaning the apical region did not differ in the groups, considering root curvature and the surgical diameter of instruments used for apical preparation. The amount of extruded material was greater in canals with mild curvature that were prepared with the 45.02 surgical instrument diameter.
Keywords: Apical extrusion; Root canal cleaning; Rotary instrumentation; biomedical and dental materials; water; anatomy; clinical trial; comparative study; contrast medium extravasation; controlled clinical trial; controlled study; endodontics; equipment design; histology; human; image processing; incisor; instrumentation; methodology; microscopy; periodontium; randomized controlled trial; tooth pulp; tooth root; Anatomy, Cross-Sectional; Dental Pulp Cavity; Equipment Design; Extravasation of Diagnostic and Therapeutic Materials; Humans; Image Processing, Computer-Assisted; Incisor; Microscopy; Periapical Tissue; Root Canal Irrigants; Root Canal Preparation; Tooth Apex; Water